Perceived Effect of Practice on Secondary School Chemistry Students: the Case Study of Selected Schools in the Ovia North Eastlocal Government Area, Edo State, Nigeria. (London Journal of Research In Humanities and Social Sciences, 2023)
This study investigated the perceived effect of practical senior secondary school student' performance in chemistry: the case study of selected schools in Ovia North East Local government area, Edo state. To achieve this purpose, three research questions were raised. The study design was quasi-experimental, using pre-test and post-test approaches. The study population consisted of all public senior secondary schools in the Ovia North East Local Government, Edo State, while the study sample size was 400 students drawn from the twenty- seven (27) public senior secondary schools in the local government area. Simple random sampling techniques was used to select fourteen school representing fifty percent. Purposive sampling was used to select 400 students from the fourteen schools. The instrument for the study was an achievement test drawn from past questions from the West African Examinations Council (WAEC) and the National Examinations Council (NECO). Two teachers of Chemistry and three Measurement and Evaluation experts validated the test items. The reliability of the instrument was checked using the Kuder-Richardson formula 20 reliability statistics and gave an index of 0.89. The collected data were analyzed using the mean and standard deviation, the t-test, and a two-way analysis of variance.
Keywords: postmodernity; objective values; subjective values; history.